PENGARUH CURRENT ASSETS, SALES DAN LIABILITAS TERHADAP LABA BERSIH PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Gunawan, Slamet; Khairiyani; Elvia Zahara , Anzu (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of current assets, sales, and liabilities on net income in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2019 -2022. This study uses independent variables, namely current assets, sales, and liabilities. The dependent variable is net income. The data used in this study is secondary data, namely in the form of financial reports of food and beverage manufacturing companies listed on the IDX for 2019-2022. 2019 is used to compare 2020 to 2022. This research is descriptive with a quantitative approach. Statistical methods using multiple linear regression analysis, t test, f test, and analysis of the coefficient of determination. The results of this study indicate that current assets have a significant effect on net income, sales have a significant effect on net income, and liabilities partially have no significant effect on net income. Then current assets, sales, and liabilities simultaneously affect net income. By using the F test it is found that the independent variables have a simultaneous influence on the dependent variable. The calculation of the coefficient of determination shows that all independent variables are 0.485 or 48.5% meaning that net income can be explained by current assets, sales and liabilities of 48.5%. while the remaining 51.5% can be explained by other factors outside of this study.